2013
DOI: 10.1590/s1413-70542013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of torrefied and carbonized briquettes of residues from coffee grain processing

Abstract: The use of biomass has been recognized as a potential renewable energy and an alternative substitute that contributes to the decrease of fossil fuels consumption. Therefore, this research aimed to analyze the thermal behavior of briquettes made of residues from coffee grain processing in different conditions: in natura, torrefied and carbonized. Eucalyptus sawdust was used for comparison. The briquettes were carbonized considering final temperature of 450° C (kept for 30 min). The briquettes torrefaction was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
3
14
1
4
Order By: Relevance
“…It was observed that ARTOK has a lower mass loss rate than AROK due to a higher resistance to thermal degradation. Fuels with higher contents of FC and low volatile matter tend to decompose slowly and offer higher resistance to thermal degradation [65]. This is in agreement with Ren et al [66] who noticed that the raw biomass lost mass faster than torrefied biomass during the pyrolysis of woody biomass.…”
Section: Kinetic Parameterssupporting
confidence: 86%
“…It was observed that ARTOK has a lower mass loss rate than AROK due to a higher resistance to thermal degradation. Fuels with higher contents of FC and low volatile matter tend to decompose slowly and offer higher resistance to thermal degradation [65]. This is in agreement with Ren et al [66] who noticed that the raw biomass lost mass faster than torrefied biomass during the pyrolysis of woody biomass.…”
Section: Kinetic Parameterssupporting
confidence: 86%
“…The procedure used in the laboratory for carbonization is similar to that found in the literature for wood (ASSIS et al, 2012;PROTÁSIO et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the solid fraction resulting from combustion of this macromolecule is approximately 9% higher than the other structural components of plant biomass (KAI et al, 2011). Furthermore, the fixed carbon is the fraction of the fuel that burns in the solid state and, thus, provides major thermal stability and less weight loss of the biomass during of the combustion (PROTÁSIO et al, 2013).…”
Section: Fresh Biomassmentioning
confidence: 99%
“…The dried leaves were then carbonized by using a furnace to decompose the chemical content of materials such as cellulose, hemicellulose, and lignin. In general, the carbonization process was done at a temperature of 250 -450°C [7]. In this study, the carbonization process was carried out at a temperature of 260°C.…”
Section: Methodsmentioning
confidence: 99%